Research on single snapshot DOA estimation algorithm based on incompletely overlapped signal - Mingchao QU; Weijian SI; Yazhi YUAN (Tongxin xuebao)
To address the problem that traditional direction-of-arrival （DOA） estimation algorithms did not fully utilize the signal characteristics of active decoys and radar， which led to poor angular resolution of anti-radiation missile， a single snapshot direction finding algorithm for polarization sensitive array based on incompletely overlapped signals was proposed.Specifically， the signal data received by the array was firstly processed by polarization smoothing.After that， exploiting the signal characteristics of incompletely overlapped signals of radar and active decoys， the constructed conjugate replication augmented matrix was differentiated to obtain each signal’s conjugate replication augmented matrix.Finally， DOA estimation results of each signal were acquired by solving a convex optimization problem.Numerical results demonstrate that the proposed method shows superior estimation accuracy and lower computational complexity compared with the conventional algorithms.